2004
DOI: 10.2337/diabetes.53.9.2509
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Erythropoietin Stimulates Angiogenesis and Wound Healing in the Genetically Diabetic Mouse

Abstract: The effects of recombinant human erythropoietin (rHuEPO) in diabetes-related healing defects were investigated by using an incisional skin-wound model produced on the back of female diabetic C57BL/KsJm ؉/؉ Lept db mice (db ϩ /db ϩ ) and their normoglycemic littermates (db ϩ/ϩ m). Animals were treated with rHuEPO (400 units/kg in 100 l s.c.) or its vehicle alone (100 l). Mice were killed on different days (3, 6, and 12 days after skin injury) for measurement of vascular endothelial growth factor (VEGF) mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
131
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 29 publications
3
131
0
1
Order By: Relevance
“…Various aspects of EPO action in rodent models have been documented, including prevention of diabetes-induced podocyte damage (Schiffer et al 2008), enhancement of wound healing (Galeano et al 2004), and promotion of vascular cell viability (Chong et al 2007). Taken together, our findings single out EPO as a potential novel glucose regulator.…”
Section: Discussionmentioning
confidence: 99%
“…Various aspects of EPO action in rodent models have been documented, including prevention of diabetes-induced podocyte damage (Schiffer et al 2008), enhancement of wound healing (Galeano et al 2004), and promotion of vascular cell viability (Chong et al 2007). Taken together, our findings single out EPO as a potential novel glucose regulator.…”
Section: Discussionmentioning
confidence: 99%
“…All tissue sections for each specimen ($20) were systematically examined using a modified histological scoring system according to data in the literature. 3 The histological parameters were examined and scored as wound closure in the form of assessment of the remaining wound area and re-epithelialization (presence or absence of epithelial covering, degree of epithelial covering relative to the number of epithelial cell layers as a monolayer or multilayer, and presence of conical structures).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In contrast with topical application of other growth factors used clinically for wound care, recombinant human erythropoietin (rhEPO) plays an important role in revascularization during the early and late stages of injury and increases the capillary density in damaged wound areas. In recent years, several studies have been conducted in which rhEPO was used successfully to stimulate angiogenesis and enhance wound healing, for example, by systemic application in both normal and genetically diabetic mice, 3,4 via topical treatment in a diabetic rat model, 5 and in our previous study of acute and chronic wounds in humans. 6 Moreover, a number of studies have reported that rhEPO affects the proliferation and differentiation of erythroid progenitor cells in hematopoietic organs, as well as nonhematopoietic cell types and organs, and plays a central role in tissue protection.…”
Section: Introductionmentioning
confidence: 99%
“…For in vivo microscopic analyses, they were applied in association with the dorsal skinfold chamber because of the excellent comparability with previous investigations [3,4,8,32]. Growth factors were not used in the present study, although several successful applications in diabetic animals have been described [39]. However, the incorporation of growth factors is extremely complicated as it concerns dosage and combinations [40].…”
Section: Discussionmentioning
confidence: 98%